Secure State Estimation of Nonlinear Cyber-Physical Systems Against DoS Attacks: A Multiobserver Approach - Yan, Jing-Jing; Yang, Guang-Hong (IEEE transactions on cybernetics, 2023)
This article focuses on the problem of secure state estimation for cyber-physical systems (CPSs), whose physical plants are modeled as nonlinear strict-feedback systems. The measured output is sent to the designed observer over a wireless communication network subject to denial-of-service (DoS) attacks. Due to the energy constraints of the attackers, the attack duration is upper bounded. Under DoS attacks, the transmission is prevented, which worsens the estimation accuracy of the existing nonlinear observers significantly. To maintain the estimation performance, a novel multiobserver scheme and a switched algorithm are proposed by introducing the hold-input mechanism and the cascade observer technique. In comparison to the existing results, where the estimation error systems may be unstable during the attack time interval, the estimation error of the designed observer converges exponentially, such that the estimation performance is improved effectively. Finally, the theoretical findings are illustrated by simulation results.